Cable in the Black Sea water, or a mysterious green energy project - Nyikos, Attila (Közigazgatási és Infokommunikációs Jogi PhD Tanulmányok, 2026)
Hungary, Romania, Georgia and Azerbaijan are planning to build a 1150 km long seabed electricity cable under the Black Sea, to transport renewable energy from the South Caucasus region into the European Union and mostly to the Hungarian electricity market. Apart from the political, economical, and technical/engineering risks and challanges to the project, EU legal barriers also pose huge problems to this enterprise. This article tries to walk the reader around the multi-angle problematics of a very complex construction project at the periphery of the European Union.